THE INTERPLAY OF SEX, POLITENESS, AND STEREOTYPES IN LINGUISTIC COMMUNICATION IN ENOLA HOLMES - Juwita Permatasari; Putri Adelia, Inayah Safani, Gracya Sibarani, Meisuri (International Journal of Teaching and Learning, 2025)
politeness, and stereotypes in Enola Holmes (2020) and Enola Holmes 2 (2022), focusing on Enola's interactions with Sherlock and Mycroft Holmes. Using Brown and Levinson's (1987) politeness theory and Butler’s (1990) gender performativity framework, the research analyzes how Enola employs politeness and directness to navigate social expectations. The findings reveal that Enola challenges traditional gender stereotypes by using assertive language with Sherlock, countering the idea that women are inherently indirect and deferential. Her polite exchanges with Mycroft, meanwhile, demonstrate that politeness can function as resistance, not just submission. This analysis highlights the adaptability of gendered communication, where politeness and assertiveness are used contextually rather than being tied to sex. Ultimately, the research shows how media like Enola Holmes both reflects and challenges societal expectations about gendered communication, oflering a more nuanced view of language, gender, and power.